Condition of the endodontic structures after vital pulpectomy (experimental study) - V. V. Afanasiev; M. A. Postnikov; D. A. Trunin; N. V. Pankratova; I. A. Zakharova; V. A. Razumni (Эндодонтия Today, 2019)
Experimental studies were conducted on 14 mongrel dogs 2-5 years old, weighing from 3 to 12 kg. Vital pulpectomy was performed with intravenous anesthesia of sodium thiopental. All animals whose teeth were examined were divided into 3 groups depending on the method of vital pulpectomy. At 10, 20 and 30 days, features of the wound process in the periapical tissues were determined. After decalcination using trilon B we made serial sections 7 μm thickness. The preparations were stained with hematoxylin-eosin or picrofuchsin according to Van Gieson after pouring into paraffin. The traditional method of vital pulpectomy leads to an acute inflammatory reaction in the complex of periapical tissues - a periodontal and bone edema, necrosis of the connective tissue, an osteoclastic reaction. Residual effects of inflammation persist after 20 days. After 30 days the signs of resorption of necrotic tissues, the formation of granulation tissue and the formation of coarse-fibrous tissue with persisting inflammation were established. When using low-frequency ultrasonic and solcoseryl, there was an inflammatory reaction in the periodontal tissue, with predominant preservation of fibrous structures with no signs of necrosis. No signs of inflammation were found in bone tissue, cement and dentin.